A comparison of suspended particle size and sediment loading produced by artificial and seaweed diets in integrated flow-through and re-circulating aquaculture systems on a commercial South African abalone farm - Potgieter, Michelle (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 36-41).